Afectación de los derechos constitucionales de los servidores públicos por efecto de aplicación del decreto ejecutivo no. 813 - Maldonado Rengel, Camilo Alonso (2016)
This thesis comprises a detailed study of the constitutional legal issue that involves the allocation of the constitutional rights of public servants , the effect of the application under Section 8 of Executive Order No. 813 , which refers to mandatory waiver the job , figure that is absolutely foreign to the State constitutional rights , and the right to job security that is enshrined as the first guarantee of public servants in Article 23 , paragraph a ) of the Constitution and is also inconsistent with the waiver based on the offer of a stimulus from the state to benefit from plans retrenchment or voluntary separation . A deep study on the unconstitutionality of Article 8 of Executive Order No. 813 is performed , from which entails the violation of constitutional rights , labor stability, legal security, due process, the right to life dignified , and very clear so contravenes the principle of inalienability of labor rights that establish the Arts. 229 and 236, paragraph 2, of the Constitution of the Republic , promoting the implementation of an executive decree on constitutional law , which contravenes the principle of regulatory hierarchy established by Article 424 of the Constitution. This study supports the completion of the field work that includes a survey counted thirty people between public and knowledgeable lawyers servers, as well as an interview with five experts on the subject. Finally, conclusions, recommendations and proposals for legal reform are made.